Analisis Pengaruh Tanaman Vetiver Terhadap Stabilitas Lereng - Putri Kurniawati (Politeknik Negeri Jakarta, 2020)
This research analyzed the influence of vetiver strengthening on slope stability. The research do in prototype media, where the slope was planned 80°. Before planting vetiver, firstly original soil is tested by index and engineering properties test. Based on the test, we can conclude that the soil use is silty clay with the value of qu and cohesion of prototype with 3 vetiver are 0,322 kg/cm2 and 0,085 kg/cm2. In prototype with 6 vetiver, the value of qu and cohesion are 0,329 kg/cm2 and 0,025 kg/cm2. Vetiver planted and tested by direct shear and unconfined compression test at planting time 4 - 7 and 16 weeks. At 16 week, the value of qu and cohesion of prototype with 3 vetiver are 0,714 kg/cm2 and 0,306 kg/cm2. In prototype with 6 vetiver, the value of qu and cohesion are 0,782 kg/cm2and 0,325 kg/cm2. The test result parameters are used as inputs to GeoStudio. Based on the program, in prototype with 3 vetiver, the safety factor increase from 0,516 to 1,519, and in prototype with 6 vetiver the safety factor increase from 0,201 to 1,545. So, it can be concluded that vetiver can improve slope stability.